A BIBLIOMETRIC ANALYSIS ON ACADEMIC STRESS AMONG UNDERGRADUATES IN MALAYSIAN PUBLIC UNIVERSITIES - Abu Kasim, Naimah; Elias, Nor Hanim; Ghazali, Siti Fadhilah; Ismail, Suharne; Mohd Najib, Nabilah Wafa’; Abdullah, Nurul Khofifah; Basarud-din, Siti Khalilah; Muhamad, Fatimah Noni; Abd Rahim, Norhafiza; Mustafa, Wan Azani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Academic stress has emerged as a critical concern affecting the mental health and academic performance of undergraduate students, particularly within the context of Malaysian public universities. Despite a growing body of literature addressing this issue, a comprehensive bibliometric analysis examining publication trends, scholarly impact, and research collaboration is still lacking. This study aims to fill that gap by systematically analyzing the scientific landscape on the causes of academic stress among undergraduates in Malaysian public universities. The main research focus involved three key keywords: “academic stress,” “mental illness,” and “undergraduate.” Using the Scopus database, a total of 813 peer-reviewed journal articles published between 2005 and 2025 were retrieved based on specific inclusion criteria namely, English-language journal articles excluding books, reviews, and conference proceedings. The data were cleaned and standardized using OpenRefine, and further analyzed through Scopus Analyzer for general trends and VOSviewer software for visualizing co-authorship networks, keyword co-occurrence, and countries collaborations. The results reveal a consistent increase in publication output over the years, with a significant concentration of research contributions from the United States, China, Australia, and Malaysia. “Academic stress,” “mental illness,” and “undergraduate students” were the most frequently occurring keywords, highlighting the central themes within this research domain. Additionally, keyword mapping and co-authorship analysis demonstrated growing interdisciplinary and international collaboration in this field. This study offers a comprehensive overview of the intellectual structure and research evolution concerning academic stress among undergraduates in Malaysia, and serves as a valuable reference for researchers, educators, and policymakers aiming to address this growing academic and psychological challenge.